2000
DOI: 10.1016/s0042-6989(99)00248-5
|View full text |Cite
|
Sign up to set email alerts
|

The time-course of pop-out search

Abstract: Olds, Cowan and Jolicoeur [2000. Tracking visual search over space and time. Psychonomic Bulletin & Review (in press)] interrupted pop-out search by adding distractors to a display after a delay. They analyzed the response time distributions from conditions with different delays for interruption and showed that when pop-out search fails, its partially completed computations can be used to assist other, slower search processes. This paper demonstrates that expectancies, numbers of items and colors in the displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
44
3
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 19 publications
6
44
3
2
Order By: Relevance
“…Olds, Cowan and Jolicoeur, 2000;Nothdurft, 2000). If these masking items appear too quickly, then pop-out is prevented.…”
Section: Fig 1 About Here ------------------------------------------mentioning
confidence: 99%
“…Olds, Cowan and Jolicoeur, 2000;Nothdurft, 2000). If these masking items appear too quickly, then pop-out is prevented.…”
Section: Fig 1 About Here ------------------------------------------mentioning
confidence: 99%
“…On a much broader time scale than that used in Olds et al's (2000aOlds et al's ( , 2000b experiments, Humphreys (1997, 2002) presented one set of colored distractors for a full second before adding to the display a set of different-colored distractors plus the target. They found that participants seemed to remember which distractors had already been discarded as nontargets during that initial second and thus were able to locate the target very efficiently.…”
mentioning
confidence: 99%
“…This process can be facilitated by at least two kinds of help-search assistance and visual marking-that seem to work by narrowing down the set of locations at which the target might be found. For example, in the experiments conducted by Olds et al (2000aOlds et al ( , 2000b and Humphreys (1997, 2002), the visual display was incrementally delivered, providing information about locations that no longer needed to be considered and narrowing the search through a restriction in the number of relevant locations.…”
mentioning
confidence: 99%
“…The results of these experiments provide basic constraints that must be satisfied by any model of early vision and visual selection. Because all visual processing is affected by which portions ofthe visual field these early mechanisms select for further analysis, it is important to determine the nature ofeach selection mechanism, as well as interactions between the mechanisms.All of the results of Olds et al (2000aOlds et al ( , 2000b were based on experiments in the color domain. Are the results specific to color, or can they be generalized to other stimulus dimensions?…”
mentioning
confidence: 99%
“…All of the results of Olds et al (2000aOlds et al ( , 2000b were based on experiments in the color domain. Are the results specific to color, or can they be generalized to other stimulus dimensions?…”
mentioning
confidence: 99%